KAJIAN BAURAN PEMASARAN DAN MANAJEMEN PENGETAHUAN TERHADAP LOYALITAS KONSUMEN DALAM INOVASI PT. TRANS RETAIL INDONESIA (CARREFOUR CITRA GARDEN MEDAN) - ANTONIUS ARITONANG (LP2MTBM MAKARIOZ, 2020)
PT. Trans Retail Indonesia focuses on management of marketing mix in 4 elements: (1) product, (2) promotion, (3) venue,and (4) price. Only provide a 48.78% contribution to customer loyalty. That is, there are 80.1% of other factors affectingcustomer loyalty. Therefore, even if the marketing mix is able to increase loyalty, the company should pay more attention toother factors that affect the customer loyalty increasing. The results of this research were supported by previous researchconducted by Kembaren (2010), Bernard (2011), and Ahmad Faizul (2010) who concluded that the simultaneous marketingvariables have positive and significant impact on customer loyalty. This reinforces that the service marketing mix programclosely relates to customer loyalty levels. Payne (in Hurriyati, 2012:42) says